EXTH-09. TUMOR PHARMACOKINETICS, PHARMACODYNAMICS AND RADIATION SENSITIZATION IN PATIENT-DERIVED XENOGRAFT MODELS OF GLIOBLASTOMA TREATED WITH THE AURORA KINASE A INHIBITOR LY3295668. (12th November 2021) - Mehta, Shwetal; Tovmasyan, Artak; Tien, An-Chi; Holter, Michael; Hopkins, Barbara; Margaryan, Tigran; Chang, Yu-Wei; Himes, Sarah; Elliott, Mackenna; Melendez, Ernesto Luna; Pennington-Krygier, Chelsea; White, Connor; et al.
Abstract: Cell-cycle deregulation is at the crux of all malignancies, including glioblastoma (GBM). Aurora Kinase A (AURKA) plays a central role in G2/M transition and faithful chromosome segregation. In this study, we evaluated the pharmacokinetics, pharmacodynamics, and radiation sensitization properties of LY3295668, a highly specific AURKA inhibitor, in orthotopic patient-derived xenograft (PDX) models of GBM. Mice with intracranial tumors were randomized to 50 mg/kg LY3295668 PO BID x 4 days vs. placebo. LY3295668 levels in plasma and contrast-enhancing tumor tissue were measured by liquid chromatography tandem mass spectrometry (LC-MS/MS). Unbound fractions were determined by equilibrium dialysis. Immunohistochemistry was performed to assess levels of pAURKA (T288), phospho-Histone H3 (pHH3), and cleaved caspase 3 (CC3). For survival studies, mice with intracranial tumors were randomized to four cohorts – vehicle, radiotherapy, LY3295668 monotherapy, and LY3295668 plus radiotherapy. The median unbound concentration of LY3295668 was 270.88 nmol/L and 22.33 nmol/kg in plasma and tumor tissue, respectively – significantly higher than the biochemical IC50 of LY3295668 for AURKA inhibition (0.8 nM). A decrease in pHH3(+) cells (0.8% vs. 6.4%, p=0.036) indicated drug-induced mitotic arrest and was accompanied by an increase in CC3(+) cells (6.4% vs. 8.0%, p=0.67). Combination of LY3295668 with radiotherapy prolonged survival compared to either therapy alone in orthotopic GBM PDX models. LY3295668 is well tolerated, achieves pharmacologically-relevant unbound concentrations in GBM PDX models, and is associated with significant target modulation. Preclinical combination of LY3295668 with radiation therapy leads to synergistic effects and supports future clinical study of this multimodal strategy in glioblastoma patients.